Association Between the Characteristics of Organizations and Their Profile of Performance Against Quality Benchmarks for Workplace Health Promotion. Issue 5 (May 2019) - Weaver, GracieLee M.; Bibeau, Daniel L.; Dudley, William N.; Bray, Jeremy; Rulison, Kelly
Abstract : Objective: This study explored subgroups of performance profiles measured by organizations' Well Workplace Checklist (WWC) benchmark scores and examined company characteristics associated with performance subgroups. Methods: The sample included 3728 US organizations that completed the WWC in 2008 to 2015. Latent profile analysis (LPA) was used to extract distinct subgroups of organizations based on benchmark performance. Multinomial logistic regression analysis was used to examine associations between the characteristics of organizations and their performance subgroup. Results: Three distinct subgroups of performance resulted from the LPA. Significant associations were found between subgroup assignment and characteristics such as size, industry, how WHP initiatives were paid for, and reasons for implementing WHP initiatives. Conclusion: The characteristics associated with subgroups of performance suggest utility for developing specific interventions tailored to different types of organizations to improve their overall quality of WHP initiatives.